2019
DOI: 10.1001/jamanetworkopen.2019.8898
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pheochromocytoma-Specific Morbidity and Mortality Among Adults With Bilateral Pheochromocytomas Undergoing Total Adrenalectomy vs Cortical-Sparing Adrenalectomy

Abstract: Key Points Question Is cortical-sparing adrenalectomy associated with increased pheochromocytoma-specific morbidity and mortality for patients with bilateral pheochromocytomas compared with total adrenalectomy? Findings In this cohort study of 625 patients with bilateral pheochromocytomas, most had hereditary syndromes, but 36% initially presented with unilateral pheochromocytoma. Bilateral total adrenalectomy resulted in a high rate of adverse effects from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 31 publications
4
59
0
8
Order By: Relevance
“…A recent international retrospective population-based study conducted by 30 academic medical centers (including our center) showed that, compared to total adrenalectomy, the rate of PHEO recurrence after ASS was comparable, whereas the risk of postoperative adrenal insufficiency and steroid dependency was significantly lower (87 vs. 43%; P = 0.03) ( 90 ). These results indicated that ASS is a highly successful treatment approach of choice that can reduce the frequency of complications and should be considered for all MEN2-related PHEO, although ASS was considered as an alternative procedure to adrenalectomy in the ATA-2015 guidelines ( 11 , 90 , 91 ). There are several issues that should be considered when selecting ASS as a treatment option ( 2 , 11 , 57 , 90 ).…”
Section: P Strategies For Management Of Men2mentioning
confidence: 99%
“…A recent international retrospective population-based study conducted by 30 academic medical centers (including our center) showed that, compared to total adrenalectomy, the rate of PHEO recurrence after ASS was comparable, whereas the risk of postoperative adrenal insufficiency and steroid dependency was significantly lower (87 vs. 43%; P = 0.03) ( 90 ). These results indicated that ASS is a highly successful treatment approach of choice that can reduce the frequency of complications and should be considered for all MEN2-related PHEO, although ASS was considered as an alternative procedure to adrenalectomy in the ATA-2015 guidelines ( 11 , 90 , 91 ). There are several issues that should be considered when selecting ASS as a treatment option ( 2 , 11 , 57 , 90 ).…”
Section: P Strategies For Management Of Men2mentioning
confidence: 99%
“…In patients with hereditary PCCs, cortical sparing surgery should always be considered since there is frequently a high risk of bilateral PCCs in hereditary disease, and cortical-sparing surgery was not associated with decreased survival despite PCC recurrence in 13% of cases in a very recently published study [103].…”
Section: Therapymentioning
confidence: 99%
“…Bei Phäochromozytomen spielen, insbesondere bei Patienten mit einer genetischen Prädisposition, nebennierenparenchymerhaltende Eingriffe eine größere Rolle. Aktuell kann jedoch die „Cortical-sparing“-Variante [ 20 ] einer Adrenalektomie nicht als solche im EUROCRINE®-Register angegeben werden. Diese Resektionen finden sich unter „andere Nebenniereneingriffe“ wieder (Tab.…”
Section: Diskussionunclassified